Sarcoidosis in a patient clinically diagnosed with silicosis; is silica associated sarcoidosis a new phenotype?. (2019) - Beijer, Els; Meek, Bob; Kromhout, Hans; van Es, H. Wouter; Seldenrijk, Kees; Drent, Marjolein; Rooijackers, Jos M.; Veltkamp, Marcel
Abstract: A diagnosis of silicosis is made on the basis of exposure and typical radiological findings, according to the ILO's International Classification of Radiographs of Pneumoconiosis. Radiological patterns of silicosis can, however, resemble sarcoidosis. Sarcoidosis is a multi-systemic disorder of unknown etiology, although a role for initiating inorganic triggers such as metals or silica has been suggested. In this case report, we illustrate a patient previously diagnosed with silicosis based on exposure and radiological features, progressive under immunosuppressive treatment. In view of these findings, an open lung biopsy was performed and revealed sarcoidosis. The patient was effectively treated with infliximab. Further analysis showed the presence of silica in the granulomas. Sensitization to silica was also demonstrated, suggesting an association between silica exposure and sarcoidosis in this patient.